2020
DOI: 10.15252/emmm.201911223
|View full text |Cite
|
Sign up to set email alerts
|

Safe eradication of large established tumors using neovasculature‐targeted tumor necrosis factor‐based therapies

Abstract: Systemic toxicities have severely limited the clinical application of tumor necrosis factor (TNF) as an anticancer agent. Activity-on-Target cytokines (AcTakines) are a novel class of immunocytokines with improved therapeutic index. A TNF-based AcTakine targeted to CD13 enables selective activation of the tumor neovasculature without any detectable toxicity in vivo. Upregulation of adhesion markers supports enhanced T-cell infiltration leading to control or elimination of solid tumors by, respectively, CAR T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…This differential expression pattern with respect to healthy tissues makes of CD13 an attractive target for the selective delivery of drugs or cytokines. Indeed, a CD13-specific single monomeric variable antibody domain tagged to tumor necrosis factor (TNF) or interferon (IFN)-γ has been used to kill tumors by targeting the tumor neovasculature [41]. In addition, peptides based in the NGR motif, found out in a phage display exercise to selectively bind CD13 [42], have already been tested in "tumor homing" strategies for chemotherapeutic agents (compiled in [3]) directed towards CD13-expressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…This differential expression pattern with respect to healthy tissues makes of CD13 an attractive target for the selective delivery of drugs or cytokines. Indeed, a CD13-specific single monomeric variable antibody domain tagged to tumor necrosis factor (TNF) or interferon (IFN)-γ has been used to kill tumors by targeting the tumor neovasculature [41]. In addition, peptides based in the NGR motif, found out in a phage display exercise to selectively bind CD13 [42], have already been tested in "tumor homing" strategies for chemotherapeutic agents (compiled in [3]) directed towards CD13-expressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, similar approaches inducing "immunological reaction towards connective tissue" could be applied to situations where scarring or fibrosis has ensued, and the breakage of the fibrosis is desirable without side effects in the rest of the body. Most recently, the technology to target powerful cytokines was further refined by generating novel "designer cytokines" that have reduced systemic toxicity to one afforded by the selective delivery to target organ [85,86]. Namely, these "designer cytokines", TNFα and interferon-γ (IFNγ) are delivered to the angiogenic vasculature by a separate vascular targeting domain [85].…”
Section: Systemically Administered Anti-fibrotic Molecule Car-decorinmentioning
confidence: 99%
“…Most recently, the technology to target powerful cytokines was further refined by generating novel "designer cytokines" that have reduced systemic toxicity to one afforded by the selective delivery to target organ [85,86]. Namely, these "designer cytokines", TNFα and interferon-γ (IFNγ) are delivered to the angiogenic vasculature by a separate vascular targeting domain [85]. In addition to that, they have a mutated receptor binding site in the therapeutic molecule, i.e.…”
Section: Systemically Administered Anti-fibrotic Molecule Car-decorinmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, we demonstrated that AcTakines based on type I interferon (IFN), targeted to type I cross-presenting dendritic cells (DCs) 30 or tumor cells 31 , induce tumor eradication in mice without systemic side effects. More recently, we showed that treatment with a tumor necrosis factor (TNF)-based AcTakine targeted to CD13 allows for destruction of large established tumors without detectable toxicity in vivo 32 .…”
Section: Introductionmentioning
confidence: 99%